Immunostimulatory effects of the standardized extract of Tinospora crispa on innate immune responses in Wistar Kyoto rats - Ahmad W; Jantan I; Kumolosasi E; Abbas Bukhari SN (Dove Medical Press, 2015)
Waqas Ahmad, Ibrahim Jantan, Endang Kumolosasi, Syed Nasir Abbas Bukhari Drug and Herbal Research Centre, Faculty of Pharmacy, Universiti Kebangsaan Malaysia, Jalan Raja Muda Abdul Aziz, Kuala Lumpur, Malaysia Abstract: Tinospora crispa (TC) has been used in folkloric medicine for the treatment of various diseases and has been reported for several pharmacological activities. However, the effects of TC extract on the immune system are largely unknown. Therefore, the present study was aimed to investigate the immunomodulatory effects of a standardized 80% ethanol extract of the stem of TC on innate immune responses. Male Wistar Kyoto rats were treated daily at 100 mg/kg, 200 mg/kg, and 400 mg/kg doses of the extract for 21 days by oral gavage. The immunomodulatory potential of TC was evaluated by determining its effect on chemotaxis and phagocytic activity of neutrophils isolated from the blood of rats. To further elucidate the mechanism of action, its effects on the proliferation of T- and B-lymphocytes and T-lymphocytes subsets (CD4+ and CD8+) and on the secretion of Th1 and Th2 cytokines were also monitored. The main components of the extracts, syringin and magnoflorine, were identified and quantitatively analyzed in the extracts by using a validated reversed-phase high-performance liquid chromatography method. It was observed that the chemotactic activity of neutrophils obtained from extract-treated rats increased as compared to controls. A dose-dependent increase in the number of migrated cells and phagocytosis activity of neutrophils was observed. Dose-dependent increase was also observed in the T- and B-lymphocytes proliferation stimulated with concanavalin A (5 µg/mL) and lipopolysaccharide (10 μg/mL), and was statistically significant at 400 mg/kg (P>0.01). Apart from cell-mediated immune response, the concentrations of Th1 (TNF-α, IL-2, and IFN-γ) and Th2 (IL-4) cytokines were significantly increased in sera of rats treated with different doses as compared with the control group. From these findings, it can be concluded that TC possesses immunostimulatory activity and has therapeutic potential for the prevention of immune diseases. Keywords: Tinospora crispa standardized extract, immunostimulation, neutrophil migration, phagocytosis, lymphocyte proliferation, T-lymphocyte phenotyping, Th1/Th2 cytokines